46.1k views
2 votes
Escreva a equação na forma fatorada:b²+ 5b + 6 = 0 b² + 3b + 2b + 6 = 0 b. (b + 3) + 2. (b + 3) = 0 (b + 3 ). (b + 2 ) = 0

1 Answer

3 votes

Respuesta:

(segundo + 3) (segundo + 2) = 0

Explicación paso a paso:

Dada la expresión cuadrática b² + 5b + 6, debemos factorizarla;

b² + 5b + 6 = 0

b² + 2b + 3b + 6 = 0

b (segundo + 2) +3 (segundo + 2) = 0

(segundo + 3) (segundo + 2) = 0

Por tanto, el factor requerido es (b + 3) (b + 2) = 0

User Akdora
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.